ORGANIZATION OF TECHNOLOGY LESSONS AND USE OF INNOVATIVE TECHNOLOGIES FOR PRIMARY STUDENTS (Universal International Scientific Journal, 2026)
The content and essence of the use of innovative technologies in improving the literacy of primary school students is aimed at their practical application by substantiating them. Innovations in the process of learning primary school students are the expansion of knowledge, acquisition, processing, improvement of new methods, technologies and approaches. The process of children's learning also includes new philosophical, cognitive and scientific approaches. Innovation is a system of purposeful actions aimed at improving the quality not only in education, but also in all areas. The article discusses the formation of innovative technologies in the organization of lessons for primary school students.
Keywords: : innovative technologies, cognitive process, philosophical, cognitive-scientific approach